Anti-Inflammatory Effects of Geniposidic Acid on Porphyromonas gingivalis-Induced Periodontitis in Mice - Tetsuya Tamura; Ruoqi Zhai; Tasuku Takemura; Kazuhisa Ouhara; Yuri Taniguchi; Yuta Hamamoto; Ryousuke Fujimori; Mikihito Kajiya; Shinji Matsuda; Syuichi Munenaga; Tsuyoshi Fujita; Noriyoshi Mizuno (Biomedicines, 2022)
Periodontal disease is predominantly caused by the pathogenic bacterium Porphyromonas gingivalis that produces inflammation-inducing factors in the host. Eucommia ulmoides is a plant native to China that has been reported to reduce blood pressure, promote weight loss, and exhibit anti-inflammatory effects. Geniposidic acid (GPA) is the major component of E. ulmoides. Herein, we investigated the effects of GPA on P. gingivalis-induced periodontitis by measuring the inflammatory responses in human gingival epithelial cells (HGECs) after P. gingivalis stimulation and GPA addition in a P. gingivalis-induced periodontitis mouse model. We found that GPA addition suppressed interleukin (IL)-6 mRNA induction (33.8% suppression), IL-6 production (69.2% suppression), toll-like receptor (TLR) 2 induction, and mitogen-activated protein kinase (MAPK) phosphorylation in HGECs stimulated by P. gingivalis. Inoculation of mice with GPA inhibited P. gingivalis-induced alveolar bone resorption (25.6% suppression) by suppressing IL-6 and TLR2 production in the serum and gingiva. GPA suppressed osteoclast differentiation of bone marrow cells induced by M-CSF and sRANKL in mice (56.7% suppression). GPA also suppressed the mRNA expression of OSCAR, NFATc1, c-Fos, cathepsin K, and DC-STAMP. In summary, GPA exerts an anti-inflammatory effect on periodontal tissue and may be effective in preventing periodontal disease.